(untitled) (Fiep Bulletin - online, 2014)
Introduction : As a result of immobility caused by amputation the individual becomes unconditioned which reduces their ability to exercise , lowers your tolerance to effort . Individuals presented with respiratory muscle dysfunction , which contributes to exercise intolerance , dyspnea and hypercapnia . Respiratory muscles can improve their function in response to exercise appropriate. The measurement of maximal respiratory pressures ( MIP and MEP ) is the most common procedure to assess the force produced by the respiratory muscles , because it is a simple, sensitive and acceptable reproducibility , resulting in a global strength of the respiratory muscles. Objective : To measure lung function in individuals at levels transfemoral amputees. Methods : The sample consisted of 6 individuals with transfemoral amputation medial , 3 female and 3 male who underwent spirometry tests and manometry . They all signed an informed consent and the project was approved by the IRB of the institution. Results: Among the subjects studied 60% were normal , and 20 % showed moderate restrictive ventilatory defect by analyzing spirometric . Regarding the maximal respiratory individuals had a mean MIP -80 cm/H20 indicating decreased respiratory muscle strength and Pemax 75 cm/H20 also indicating decreased expiratory muscle strength. Conclusions: It was possible to identify the sample population has decreased ventilatory capacity and muscle strength that are derived from the consequences of immobility transfemoral amputation.